Analisis Manajemen Persediaan Barang Dagang dalam Upaya Meningkatkan Kinerja Perusahaan (Studi Kasus pada Penggilingan Padi Bumi Makmur) - Pratiwi, Agatha; Aminah (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
Inventory management is an effort to determine the size of inventory levels and control them effectively and efficiently the inventory of merchandise. This study aims to find out, test and analyze merchandise inventory management in an effort to improve the performance of Bumi Makmur Rice Milling Company for the period January to June 2022. The technique used by the author in further analyzing and finding facts is through merchandise inventory cards with the perpetual FIFO method and the calculation of company profit / loss. The results of the analysis show a significant increase in inventory from January to June 2022. The performance of Bumi Makmur Rice Milling Company as measured using profitability ratio with gross profit margin calculation also increased significantly, although in the second month it experienced a slight decline. Companies are advised to use merchandise inventory cards so that the company can know exactly the stock of inventory in the warehouse.